Farmer Evaluations Of The System Of Rice Intensification (SRI) Compared With Conventional Rice Production In Benin - Gbenou, Pascal; Mitchel, Anne-Marie; Sedami, Adjahossou B.; Agossou, Pr. Noukpo (European Scientific Journal, ESJ, 2016)
This article summarizes the evaluation of a new method for rice cultivation, the System of Rice Intensification (SRI), by a group of 90 rice farmers in Benin. Between August 2009 and June 2012, a series of tests were conducted in two rice ecosystems on 32 plots. This farmer-conducted research focused on the new methodology’s agronomic performance and its labor and seed requirements, also considering what would be the constraints on adoption. The trials showed that SRI methods could increase average yields under farmer conditions by 54 %, while reducing seed requirements by 87 % and shortening the growing season by 14 days. To achieve these benefits required an increase in the amount of labor, by 36 %. Producers participating in this evaluation concluded that SRI offers significant opportunities to increase their rice production, provided its methods are adapted to local conditions